2022
DOI: 10.1007/s13555-022-00761-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics and Treatment Patterns in European Pediatric Patients with Psoriasis: A Real-World, Cross-Sectional Study

Abstract: Introduction: This study evaluated patient characteristics and treatment patterns according to weight in pediatric patients with psoriasis in a real-world setting. Methods: Primary care and specialist physicians treating pediatric patients with psoriasis aged 6-17 years in five European countries were surveyed in the 2019-2020 Adelphi Real World Pediatric Psoriasis Disease Specific Programme. At least two patients with current or previous biologic use were included per physician. Patient characteristics and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Biologinė terapija. Europoje vidutinio sunkumo ir sunkiai vaikų psoriazei gydyti šiuo metu patvirtinta keletas biologinių vaistų (etanerceptas, adalimumabas, ustekinumabas) įskaitant ir naujesnius biologinius vaistus (iksekizumabas ir secukinumabas) [16]. Tiriami ir kiti biologiniai preparatai, tokie kaip brodalumabas [17], guselkumabas [18] ir risankizumabas [19].…”
Section: Tyrimo Rezultataiunclassified
“…Biologinė terapija. Europoje vidutinio sunkumo ir sunkiai vaikų psoriazei gydyti šiuo metu patvirtinta keletas biologinių vaistų (etanerceptas, adalimumabas, ustekinumabas) įskaitant ir naujesnius biologinius vaistus (iksekizumabas ir secukinumabas) [16]. Tiriami ir kiti biologiniai preparatai, tokie kaip brodalumabas [17], guselkumabas [18] ir risankizumabas [19].…”
Section: Tyrimo Rezultataiunclassified
“…Biologics are more likely to be prescribed in patients with moderate-to-severe PsO, overweight and with concomitant psoriatic arthritis. 32 Approximately 25% of pediatric patients with psoriasis are treated with biologics at some point in their life, and one-third of them will also simultaneously receive topical and/or conventional treatment. 32 The real-life study conducted among psoriatic patients by Marques et al 33 which included also children revealed superior effectiveness of biological medications when compared to topical and non-biological therapies, but higher rate of side effects including mild infections, which are consistent with other studies.…”
Section: Psoriasis and Pediatric Psoriasis - Introductionmentioning
confidence: 99%
“… 32 Approximately 25% of pediatric patients with psoriasis are treated with biologics at some point in their life, and one-third of them will also simultaneously receive topical and/or conventional treatment. 32 The real-life study conducted among psoriatic patients by Marques et al 33 which included also children revealed superior effectiveness of biological medications when compared to topical and non-biological therapies, but higher rate of side effects including mild infections, which are consistent with other studies. 34 European recommendations emphasize that choosing biologics for patients should be influenced by specific circumstances, such as presence of comorbidities, pregnancy or chronic infections.…”
Section: Psoriasis and Pediatric Psoriasis - Introductionmentioning
confidence: 99%